PAI TEACHER'S STRATEGY IN DEVELOPING STUDENTS' AKHLAKUL KARIMAH THROUGH MUHADHARAH ACTIVITIES - Hasani, Muhamad (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to determine the strategies used by PAI teachers and to determine the supporting and inhibiting factors in developing students' morals at Mts Daarul Ahsan Tangerang through Muhadharah activities. This research method uses qualitative methods with descriptive research type. This research found that there are three strategies for PAI teachers in developing students' morals through muhadharah activities. (1) Supervision and Monitoring (2) Habituation and Practice (3) Example. This research also found supporting and inhibiting factors in developing students' morals through muhadharah activities. Supporting factors (1) School policies and facilities that are in accordance with the development of student morals. (2) High enthusiasm from the students themselves. Inhibiting Factors (1) Obstacles arise from the students themselves. (2) Students are less orderly in carrying out muhadharah activities. The solutions taken by PAI teachers in dealing with these obstacles are (1) Giving direct warnings to students who violate (2) Holding meetings with student parents (3) Direct supervision and attendance at each muhadharah activity.